Moral value inventory for Muslim Adolescents - Abdullah S.; Salleh A.; Mahmud Z.; Ghani S.Abd. (Elsevier Ltd, 2024)
The paper reports a validity and reliability study on a newly developed Moral Value Inventory for Muslim Adolescent (MVIMA). Analysis of data using 107 subjects showed a high general relialibity (.95), and the nine sub-scales (patience, gratefulness, humility, respecfulness, positive regard, honesty, love, tawakal, sincerity and taqwa) shows reliability value ranging between .72 to .84. The convergence validity for the sub-scales were significantly correlated (.36 to .72; p<.01). Factor analysis identified four factors (self-spiritual, self-social, social-spiritual, and self). Forty eight items with factor loading between .413-.657 of 99 original items were retained in the final inventory. 2010 Published by Elsevier Ltd.